Light-transmitting soft stone and preparation method thereof

By using a combination of quartz sand, limestone, additives and modified rosin resins of a specific proportion in the light-transmitting soft stone, and using the preparation method of the modified rosin resin, the existing light-transmitting soft stone has poor light transmission effect and susceptible to heat deformation, achieving better light transmittance, strength and aging resistance, and extending service life.

CN119638269APending Publication Date: 2025-03-18佛山市西泰陶瓷科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411453692.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing light-transmitting soft stone has poor light-transmitting effect and is easily deformed by heat, resulting in a shortened service life.

Method used

The combination of 30 to 60 parts by weight of quartz sand, 40 to 60 parts of limestone, 1 to 5 parts of additives, and 10 to 30 parts of modified rosin resin is used, and a specific modified rosin resin preparation method includes stirring the rosin resin with NaOH solution, adding styrene, acrylic acid, butyl methacrylate and benzoyl peroxide for modification reaction, adjusting the pH to 7-8, and obtaining the modified rosin resin.

Benefits of technology

It achieves better light transmittance, strength and aging resistance of light-transmitting soft stone, and has a soft texture, which can be processed into a curved surface, extending its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a light-transmitting soft stone which comprises the following components in parts by weight: 30-60 parts of quartz sand, 40-60 parts of limestone, 1-5 parts of an auxiliary agent and 10-30 parts of modified rosin resin. The light-transmitting soft stone prepared by the invention has better light transmittance, better strength and aging resistance, is soft in texture and can be processed into a curved surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of light-transmitting soft stone, and in particular to a light-transmitting soft stone and a preparation method thereof. Background Art

[0002] As a new type of green building material, translucent soft stone can make comprehensive use of various resources and is a high-end decoration that replaces natural stone. It can effectively curb the over-exploitation of natural stone and promote the development of environmental protection, circular economy and low-carbon economy. At the same time, the size, specifications and thickness of translucent soft stone products can be adjusted arbitrarily, and can be cut, drilled and bonded according to actual needs, and can produce semi-translucent and fully translucent products.

[0003] Existing light-transmitting soft stones usually use natural stone particles, resins, fillers, pigments and initiators as raw materials. When using the light-transmitting soft stones, a light source needs to be placed on one side of the light-transmitting soft stones. Existing light-transmitting soft stones have poor light-transmitting effects and are easily deformed by heat, resulting in a shortened service life. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a light-transmitting soft stone which has good light transmittance, good strength and aging resistance, and is soft in texture and can be processed into a curved surface.

[0005] The technical problem to be solved by the present invention is also to provide a method for preparing light-transmitting soft stone, wherein the light-transmitting soft stone prepared by the method has good light transmittance, good strength and aging resistance, and is soft in texture and can be processed into a curved surface.

[0006] In order to solve the above problems, the present invention provides a light-transmitting soft stone, which comprises the following components by weight: 30-60 parts of quartz sand, 40-60 parts of limestone, 1-5 parts of additives, and 10-30 parts of modified rosin resin.

[0007] In some embodiments, the modified rosin resin is prepared by the following method:

[0008] Heating and softening the rosin resin, then adding the NaOH solution, and stirring for a preset time to obtain a first mixture;

[0009] After the first mixture is heated to a preset temperature, styrene, acrylic acid, butyl methacrylate and benzoyl peroxide are added thereto to carry out a modification reaction;

[0010] After the modification reaction is completed, the pH is adjusted to 7-8 to obtain modified rosin resin.

[0011] In some embodiments, the step of heating and softening the rosin resin, then adding the NaOH solution, and stirring for a preset time to obtain a first mixture comprises the following steps:

[0012] The rosin resin is heated to 90°C to 100°C,

[0013] When the rosin resin is completely softened, 4 wt% to 6 wt% NaOH solution is added and stirred for 2 h to 3 h to obtain a first mixture;

[0014] The amount of the NaOH solution added is 12 wt% to 14 wt% of the amount of the rosin resin added.

[0015] In some embodiments, after the first mixture is heated to a preset temperature, styrene, acrylic acid, butyl methacrylate and benzoyl peroxide are added thereto to carry out a modification reaction, comprising the following steps:

[0016] After the first mixture is heated to 130° C. to 135° C., a first amount of styrene, a second amount of acrylic acid, a third amount of butyl methacrylate and a fourth amount of benzoyl peroxide are gradually added dropwise within 4 to 5 hours, and then a fifth amount of benzoyl peroxide is added within 1 to 2 hours.

[0017] In some embodiments, the first addition amount is 22 wt% to 33 wt% of the addition amount of the rosin resin;

[0018] The second added amount is 13wt% to 25wt% of the added amount of the rosin resin;

[0019] The third added amount is 33wt% to 60wt% of the added amount of the rosin resin;

[0020] The fourth addition amount is 1wt% to 3wt% of the addition amount of the rosin resin;

[0021] The fifth added amount is 1 wt % to 3 wt % of the added amount of the rosin resin.

[0022] In some embodiments, the fineness of the quartz sand is 70 mesh to 120 mesh;

[0023] The fineness of the limestone is 200-235 mesh;

[0024] The auxiliary agents include thickeners, water repellents and defoamers.

[0025] In order to solve the above problems, the present invention provides a method for preparing light-transmitting soft stone, comprising the following steps:

[0026] preparing modified rosin resin;

[0027] In parts by weight, 30 to 60 parts of quartz sand, 40 to 60 parts of limestone, 1 to 5 parts of additives and 10 to 30 parts of modified rosin resin are mixed and cured to obtain translucent soft stone.

[0028] In order to solve the above problems, the present invention also provides a method for preparing light-transmitting soft stone, comprising the following steps:

[0029] preparing modified rosin resin;

[0030] By weight, 30 to 60 parts of quartz sand, 40 to 60 parts of limestone, 1 to 5 parts of additives, and 10 to 30 parts of modified rosin resin are mixed to obtain a mixed raw material;

[0031] Placing the mixed raw material into a mold to form a first blank;

[0032] performing a first drying process on the first green body to obtain a second green body;

[0033] placing a reinforcing mesh on the second green body, and then performing a second drying process to obtain a third green body;

[0034] placing a reinforcing mesh on the third green body, and then performing a third drying process to obtain a fourth green body;

[0035] After the fourth green body is demoulded, a light-transmitting soft stone is obtained.

[0036] In some embodiments, the temperature of the first drying process is 170°C to 190°C;

[0037] The temperature of the first drying process is 190°C to 210°C;

[0038] The temperature of the first drying process is 220°C to 240°C.

[0039] In some embodiments, the preparation of the modified rosin resin comprises the following steps:

[0040] Heating and softening the rosin resin, then adding the NaOH solution, and stirring for a preset time to obtain a first mixture;

[0041] After the first mixture is heated to a preset temperature, styrene, acrylic acid, butyl methacrylate and benzoyl peroxide are added thereto to carry out a modification reaction;

[0042] After the modification reaction is completed, the pH is adjusted to 7-8 to obtain modified rosin resin.

[0043] The implementation of the present invention has the following beneficial effects:

[0044] The light-transmitting soft stone provided by the present invention comprises: quartz sand, limestone, additives, and modified rosin resin. The light-transmitting soft stone has good light transmittance, good strength and aging resistance, and is soft in texture and can be processed into a curved surface by adding modified rosin resin with a specific structure. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Examples of the embodiments, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. In addition, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0046] In the description of the present invention, it is necessary to understand that the terms "length", "width", "up", "down", "left", "right", "horizontal", "top", "bottom" and the like indicating directions or positional relationships are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore should not be understood as a limitation on the present invention.

[0047] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0048] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or mutual communication; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0049] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact through another feature between them. Moreover, a first feature being "above", "above" and "above" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature includes that the first feature is directly below and obliquely below the second feature, or simply indicates that the first feature is lower in level than the second feature.

[0050] The disclosure below provides many different embodiments or examples to realize different structures of the present invention. In order to simplify the disclosure of the present invention, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplification and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed. In addition, the examples of various specific processes and materials provided by the present invention, but those of ordinary skill in the art can be aware of the application of other processes and / or the use of other materials.

[0051] In the present invention, "preferred" and "better" are only used to describe implementation methods or embodiments with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of the present invention. In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features. In the present invention, when involving numerical ranges, unless otherwise specified, the two endpoints of the numerical range are included.

[0052] In order to solve the above problems, the present invention provides a translucent soft stone, which includes the following components by weight: 30-60 parts of quartz sand, 40-60 parts of limestone, 1-5 parts of additives, and 10-30 parts of modified rosin resin.

[0053] Specifically, quartz sand is quartz particles obtained by crushing quartz stone. The main mineral component of quartz sand is silicon dioxide, which has high hardness and wear resistance and stable chemical properties. Adding a specific proportion of quartz sand to translucent soft stone can not only improve the physical strength of the translucent soft stone, but also improve the wear resistance of the translucent soft stone. In some embodiments, the exemplary weight parts of the quartz sand are 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, 42 parts, 44 parts, 46 parts, 48 ​​parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, and 60 parts, not limited to the above.

[0054] In some embodiments, the fineness of the quartz sand is 70-120 mesh; using quartz sand of the above fineness can obtain better light transmittance and surface smoothness.

[0055] Limestone is a naturally formed sedimentary rock, the main component of which is calcium carbonate. It is a widely used building material. Limestone has moderate hardness, is easy to cut and process, has good weather resistance in outdoor environments, and is cheap. Adding a specific proportion of limestone to the translucent soft stone can provide strength. In some embodiments, the exemplary weight parts of the limestone are 40 parts, 42 parts, 44 parts, 46 parts, 48 ​​parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, and 60 parts, not limited to the above enumeration.

[0056] In some embodiments, the fineness of the limestone is 200-235 meshes; using limestone with the above fineness can obtain better light transmittance and surface smoothness.

[0057] In some embodiments, the additives include thickeners, hydrophobic agents, and defoamers. The thickeners include carboxymethyl cellulose and sodium carboxymethyl cellulose; the hydrophobic agents include silicone hydrophobic agents and fluorocarbon hydrophobic agents; the defoamers include silicone oil defoamers and polyether defoamers. Adding the above additives to the translucent soft stone can stabilize the slurry and prevent the powder from sinking. In some embodiments, the exemplary weight parts of the additives are 1 part, 2 parts, 3 parts, 4 parts, and 5 parts, not limited to the above.

[0058] Most importantly, the present invention adds a self-made modified rosin resin to the light-transmitting soft stone. In some embodiments, the modified rosin resin is prepared by the following method:

[0059] Heating and softening the rosin resin, then adding the NaOH solution, and stirring for a preset time to obtain a first mixture;

[0060] After the first mixture is heated to a preset temperature, styrene, acrylic acid, butyl methacrylate and benzoyl peroxide are added thereto to carry out a modification reaction;

[0061] After the modification reaction is completed, the pH is adjusted to 7-8 to obtain modified rosin resin.

[0062] It should be noted that NaOH is added to dissolve the rosin resin in water, styrene, acrylic acid and butyl methacrylate are added to modify the rosin resin, and benzoyl peroxide is a polymerization initiator.

[0063] In some embodiments, the step of heating and softening the rosin resin, then adding the NaOH solution, and stirring for a preset time to obtain a first mixture comprises the following steps:

[0064] The rosin resin is heated to 90°C to 100°C,

[0065] When the rosin resin is completely softened, 4 wt% to 6 wt% NaOH solution is added and stirred for 2 h to 3 h to obtain a first mixture;

[0066] The amount of the NaOH solution added is 12 wt% to 14 wt% of the amount of the rosin resin added.

[0067] It should be noted that the NaOH solution is added to soften the rosin resin. If too little NaOH solution is added, the rosin resin cannot be completely dissolved. If too much NaOH solution is added, the alkalinity is too strong, which affects the subsequent reactions.

[0068] In some embodiments, after the first mixture is heated to a preset temperature, styrene, acrylic acid, butyl methacrylate and benzoyl peroxide are added thereto to carry out a modification reaction, comprising the following steps:

[0069] After the first mixture is heated to 130° C. to 135° C., a first amount of styrene, a second amount of acrylic acid, a third amount of butyl methacrylate and a fourth amount of benzoyl peroxide are gradually added dropwise within 4 to 5 hours, and then a fifth amount of benzoyl peroxide is added within 1 to 2 hours.

[0070] Benzoyl peroxide is used as a polymerization initiator. Adding it in batches can ensure a more complete monomer reaction and reduce residual monomers, thereby improving the yield and quality of the product.

[0071] In some embodiments, the first addition amount is 22 wt% to 33 wt% of the addition amount of the rosin resin;

[0072] The second added amount is 13wt% to 25wt% of the added amount of the rosin resin;

[0073] The third added amount is 33wt% to 60wt% of the added amount of the rosin resin;

[0074] The fourth addition amount is 1wt% to 3wt% of the addition amount of the rosin resin;

[0075] The fifth added amount is 1 wt % to 3 wt % of the added amount of the rosin resin.

[0076] Adding the modifier and the initiator in the above amounts can obtain a modified resin with a suitable glass transition temperature.

[0077] Accordingly, the present invention provides a method for preparing light-transmitting soft stone, comprising the following steps:

[0078] preparing modified rosin resin;

[0079] In parts by weight, 30 to 60 parts of quartz sand, 40 to 60 parts of limestone, 1 to 5 parts of additives and 10 to 30 parts of modified rosin resin are mixed and cured to obtain translucent soft stone.

[0080] Furthermore, the present invention also provides a method for preparing light-transmitting soft stone, comprising the following steps:

[0081] preparing modified rosin resin;

[0082] By weight, 30 to 60 parts of quartz sand, 40 to 60 parts of limestone, 1 to 5 parts of additives, and 10 to 30 parts of modified rosin resin are mixed to obtain a mixed raw material;

[0083] Placing the mixed raw material into a mold to form a first blank;

[0084] performing a first drying process on the first green body to obtain a second green body;

[0085] placing a reinforcing mesh on the second green body, and then performing a second drying process to obtain a third green body;

[0086] placing a reinforcing mesh on the third green body, and then performing a third drying process to obtain a fourth green body;

[0087] After the fourth green body is demoulded, a light-transmitting soft stone is obtained.

[0088] In order to increase the strength of the light-transmitting soft stone, a reinforcement mesh is added in some embodiments. In some embodiments, the reinforcement mesh is made of a glass fiber mesh.

[0089] In some embodiments, the temperature of the first drying process is 170°C to 190°C; the temperature of the first drying process is 190°C to 210°C; the temperature of the first drying process is 220°C to 240°C.

[0090] It should be noted that in order for the reinforcement net to not affect the pattern of the light-transmitting soft stone, the reinforcement net needs to be added after the surface of the light-transmitting soft stone body solidifies. Therefore, a first drying treatment with a lower temperature is introduced. The low-temperature curing takes a longer time, making the surface of the light-transmitting soft stone body more balanced. Then the reinforcement net is placed to improve the strength of the light-transmitting soft stone and a second drying treatment is performed. The temperature of the second drying treatment is higher, which can shorten the curing time and improve the strength of the light-transmitting soft stone. Subsequently, another layer of reinforcement net is added and a third drying treatment is performed, which again enhances the strength of the light-transmitting soft stone and further shortens the curing time.

[0091] In some embodiments, the preparation of the modified rosin resin comprises the following steps:

[0092] Heating and softening the rosin resin, then adding the NaOH solution, and stirring for a preset time to obtain a first mixture;

[0093] After the first mixture is heated to a preset temperature, styrene, acrylic acid, butyl methacrylate and benzoyl peroxide are added thereto to carry out a modification reaction;

[0094] After the modification reaction is completed, the pH is adjusted to 7-8 to obtain modified rosin resin.

[0095] The present invention is further described below with reference to specific embodiments.

[0096] Example 1

[0097] The present embodiment provides a light-transmitting soft stone, which comprises the following components by weight: 45 parts of quartz sand, 50 parts of limestone, 3 parts of additives, and 20 parts of modified rosin resin.

[0098] The modified rosin resin is prepared by the following method:

[0099] The rosin resin is heated to 90° C., and when the rosin resin is completely softened, a 5 wt % NaOH solution is added, wherein the amount of the NaOH solution added is 13 wt % of the amount of the rosin resin added, and the mixture is stirred for 2 h to obtain a first mixture;

[0100] After the first mixture is heated to 130° C., a first amount of styrene, a second amount of acrylic acid, a third amount of butyl methacrylate and a fourth amount of benzoyl peroxide are gradually added dropwise within 5 hours, and then a fifth amount of benzoyl peroxide is added within 1 hour;

[0101] After the modification reaction is completed, the pH is adjusted to 7-8 to obtain a modified rosin resin;

[0102] The first added amount is 30wt% of the added amount of the rosin resin;

[0103] The second added amount is 20wt% of the added amount of the rosin resin;

[0104] The third added amount is 40wt% of the added amount of the rosin resin;

[0105] The fourth added amount is 1.5wt% of the added amount of the rosin resin;

[0106] The fifth added amount is 1.5 wt % of the added amount of the rosin resin.

[0107] When preparing the light-transmitting soft stone, firstly prepare the modified rosin resin solution according to the above method, then mix 45 parts of quartz sand, 50 parts of limestone, 3 parts of auxiliary agent and 20 parts of the modified rosin resin solution, and obtain the light-transmitting soft stone after solidification.

[0108] Example 2

[0109] The present embodiment provides a light-transmitting soft stone, which comprises the following components by weight: 45 parts of quartz sand, 50 parts of limestone, 3 parts of additives, and 20 parts of modified rosin resin.

[0110] The modified rosin resin is prepared by the following method:

[0111] The rosin resin is heated to 90° C., and when the rosin resin is completely softened, a 5 wt % NaOH solution is added, wherein the amount of the NaOH solution added is 13 wt % of the amount of the rosin resin added, and the mixture is stirred for 2 h to obtain a first mixture;

[0112] After the first mixture is heated to 130° C., a first amount of styrene, a second amount of acrylic acid, a third amount of butyl methacrylate and a fourth amount of benzoyl peroxide are gradually added dropwise within 5 hours, and then a fifth amount of benzoyl peroxide is added within 1 hour;

[0113] After the modification reaction is completed, the pH is adjusted to 7-8 to obtain a modified rosin resin;

[0114] The first added amount is 22wt% of the added amount of the rosin resin;

[0115] The second added amount is 13wt% of the added amount of the rosin resin;

[0116] The third added amount is 33wt% of the added amount of the rosin resin;

[0117] The fourth added amount is 1wt% of the added amount of the rosin resin;

[0118] The fifth added amount is 1 wt % of the added amount of the rosin resin.

[0119] When preparing the light-transmitting soft stone, firstly prepare the modified rosin resin solution according to the above method, then mix 45 parts of quartz sand, 50 parts of limestone, 3 parts of auxiliary agent and 20 parts of the modified rosin resin solution, and obtain the light-transmitting soft stone after solidification.

[0120] Example 3

[0121] The present embodiment provides a light-transmitting soft stone, which comprises the following components by weight: 45 parts of quartz sand, 50 parts of limestone, 3 parts of additives, and 20 parts of modified rosin resin.

[0122] The modified rosin resin is prepared by the following method:

[0123] The rosin resin is heated to 90° C., and when the rosin resin is completely softened, a 5 wt % NaOH solution is added, wherein the amount of the NaOH solution added is 13 wt % of the amount of the rosin resin added, and the mixture is stirred for 2 h to obtain a first mixture;

[0124] After the first mixture is heated to 130° C., a first amount of styrene, a second amount of acrylic acid, a third amount of butyl methacrylate and a fourth amount of benzoyl peroxide are gradually added dropwise within 5 hours, and then a fifth amount of benzoyl peroxide is added within 1 hour;

[0125] After the modification reaction is completed, the pH is adjusted to 7-8 to obtain a modified rosin resin;

[0126] The first added amount is 33wt% of the added amount of the rosin resin;

[0127] The second added amount is 25wt% of the added amount of the rosin resin;

[0128] The third added amount is 60wt% of the added amount of the rosin resin;

[0129] The fourth added amount is 3wt% of the added amount of the rosin resin;

[0130] The fifth added amount is 3 wt % of the added amount of the rosin resin.

[0131] When preparing the light-transmitting soft stone, firstly prepare the modified rosin resin solution according to the above method, then mix 45 parts of quartz sand, 50 parts of limestone, 3 parts of auxiliary agent and 20 parts of the modified rosin resin solution, and obtain the light-transmitting soft stone after solidification.

[0132] Example 4

[0133] The present embodiment provides a light-transmitting soft stone, which comprises the following components by weight: 45 parts of quartz sand, 50 parts of limestone, 3 parts of additives, and 20 parts of modified rosin resin.

[0134] The modified rosin resin is prepared by the following method:

[0135] The rosin resin is heated to 90° C., and when the rosin resin is completely softened, a 5 wt % NaOH solution is added, wherein the amount of the NaOH solution added is 13 wt % of the amount of the rosin resin added, and the mixture is stirred for 2 h to obtain a first mixture;

[0136] After the first mixture is heated to 130° C., a first amount of styrene, a second amount of acrylic acid, a third amount of butyl methacrylate and a fourth amount of benzoyl peroxide are gradually added dropwise within 5 hours, and then a fifth amount of benzoyl peroxide is added within 1 hour;

[0137] After the modification reaction is completed, the pH is adjusted to 7-8 to obtain a modified rosin resin;

[0138] The first added amount is 30wt% of the added amount of the rosin resin;

[0139] The second added amount is 20wt% of the added amount of the rosin resin;

[0140] The third added amount is 40wt% of the added amount of the rosin resin;

[0141] The fourth added amount is 1.5wt% of the added amount of the rosin resin;

[0142] The fifth added amount is 1.5 wt % of the added amount of the rosin resin.

[0143] When preparing the light-transmitting soft stone, firstly prepare the modified rosin resin solution according to the above method, then mix 45 parts of quartz sand, 50 parts of limestone, 3 parts of auxiliary agent and 20 parts of the modified rosin resin solution to obtain a mixed raw material;

[0144] Placing the mixed raw material into a mold to form a first blank;

[0145] performing a first drying process on the first green body to obtain a second green body;

[0146] placing a reinforcing mesh on the second green body, and then performing a second drying process to obtain a third green body;

[0147] placing a reinforcing mesh on the third green body, and then performing a third drying process to obtain a fourth green body;

[0148] After the fourth green body is demoulded, a light-transmitting soft stone is obtained.

[0149] The temperature of the first drying process is 180°C;

[0150] The temperature of the first drying process is 200°C;

[0151] The temperature of the first drying process is 230°C.

[0152] Comparative Example 1

[0153] This comparative example provides a light-transmitting soft stone, which comprises the following components by weight: 45 parts of quartz sand, 50 parts of limestone, 1 to 5 parts of additives, and 20 parts of rosin resin.

[0154] When preparing the light-transmitting soft stone, 45 parts of quartz sand, 50 parts of limestone, 3 parts of auxiliary agent and 20 parts of modified rosin resin solution are mixed, and the light-transmitting soft stone is obtained after solidification.

[0155] The light-transmitting soft stones obtained in Examples 1 to 4 and Comparative Example 1 were tested. The test results are shown in Table 1.

[0156] Table 1 Test results of light-transmitting soft stones prepared in Examples 1 to 4 and Comparative Example 1

[0157]

[0158]

[0159] The light-transmitting soft stone provided in Examples 1 to 4 has good light transmittance, good strength and aging resistance, and is soft in texture and can be processed into a curved surface.

[0160] In the description of this specification, the description with reference to the terms "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiments or examples are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0161] The above disclosure is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A light-transmitting soft stone, characterized in that: The invention comprises the following components in parts by weight: 30-60 parts of quartz sand, 40-60 parts of limestone, 1-5 parts of auxiliary agent and 10-30 parts of modified rosin resin.

2. The light-transmitting soft stone according to claim 1, characterized in that: The modified rosin resin is prepared by the following method: Heating and softening the rosin resin, then adding the NaOH solution, and stirring for a preset time to obtain a first mixture; After the first mixture is heated to a preset temperature, styrene, acrylic acid, butyl methacrylate and benzoyl peroxide are added thereto to carry out a modification reaction; After the modification reaction is completed, the pH is adjusted to 7-8 to obtain modified rosin resin.

3. The light-transmitting soft stone according to claim 2, characterized in that: The rosin resin is heated and softened, then a NaOH solution is added, and stirred for a preset time to obtain a first mixture, comprising the following steps: The rosin resin is heated to 90°C to 100°C, When the rosin resin is completely softened, 4 wt% to 6 wt% NaOH solution is added and stirred for 2 h to 3 h to obtain a first mixture; The amount of the NaOH solution added is 12 wt% to 14 wt% of the amount of the rosin resin added.

4. The light-transmitting soft stone according to claim 2, characterized in that: After the first mixture is heated to a preset temperature, styrene, acrylic acid, butyl methacrylate and benzoyl peroxide are added thereto to carry out a modification reaction, comprising the following steps: After the first mixture is heated to 130° C. to 135° C., a first amount of styrene, a second amount of acrylic acid, a third amount of butyl methacrylate and a fourth amount of benzoyl peroxide are gradually added dropwise within 4 to 5 hours, and then a fifth amount of benzoyl peroxide is added within 1 to 2 hours.

5. The light-transmitting soft stone according to claim 4, characterized in that: The first added amount is 22wt% to 33wt% of the added amount of the rosin resin; The second added amount is 13wt% to 25wt% of the added amount of the rosin resin; The third added amount is 33wt% to 60wt% of the added amount of the rosin resin; The fourth addition amount is 1wt% to 3wt% of the addition amount of the rosin resin; The fifth added amount is 1 wt % to 3 wt % of the added amount of the rosin resin.

6. The light-transmitting soft stone according to claim 1, characterized in that: The fineness of the quartz sand is 70 mesh to 120 mesh; The fineness of the limestone is 200-235 mesh; The auxiliary agents include thickeners, water repellents and defoamers.

7. A method for preparing light-transmitting soft stone according to any one of claims 1 to 6, characterized in that: The following steps are involved: preparing modified rosin resin; In parts by weight, 30 to 60 parts of quartz sand, 40 to 60 parts of limestone, 1 to 5 parts of additives and 10 to 30 parts of modified rosin resin are mixed and cured to obtain translucent soft stone.

8. A method for preparing light-transmitting soft stone according to any one of claims 1 to 6, characterized in that: The following steps are involved: preparing modified rosin resin; By weight, 30 to 60 parts of quartz sand, 40 to 60 parts of limestone, 1 to 5 parts of additives, and 10 to 30 parts of modified rosin resin are mixed to obtain a mixed raw material; Placing the mixed raw material into a mold to form a first blank; performing a first drying process on the first green body to obtain a second green body; placing a reinforcing mesh on the second green body, and then performing a second drying process to obtain a third green body; placing a reinforcing mesh on the third green body, and then performing a third drying process to obtain a fourth green body; After the fourth green body is demoulded, a light-transmitting soft stone is obtained.

9. The method for preparing light-transmitting soft stone according to claim 8, characterized in that: The temperature of the first drying process is 170°C to 190°C; The temperature of the first drying process is 190°C to 210°C; The temperature of the first drying process is 220°C to 240°C.

10. The method for preparing light-transmitting soft stone according to claim 7 or 8, characterized in that: The preparation of modified rosin resin comprises the following steps: Heating and softening the rosin resin, then adding the NaOH solution, and stirring for a preset time to obtain a first mixture; After the first mixture is heated to a preset temperature, styrene, acrylic acid, butyl methacrylate and benzoyl peroxide are added thereto to carry out a modification reaction; After the modification reaction is completed, the pH is adjusted to 7-8 to obtain modified rosin resin.